2018
DOI: 10.1016/j.cnp.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Utility of threshold tracking transcranial magnetic stimulation in ALS

Abstract: HighlightsThe threshold tracking transcranial magnetic stimulation [TMS] technique provides valuable insights into ALS pathogenesis.Cortical hyperexcitability identifies the disease site origin and subsequent spread.Threshold tracking TMS holds great promise as an ALS biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 144 publications
5
64
1
Order By: Relevance
“…In Experiment 1, based on the corresponding literature, the hunting-threshold was defined as the TS intensity (expressed in percentage of the maximal stimulator output (%MSO)) required to elicit a MEPtarget in the relaxed FDI of 0.2 mV in peak-to-peak amplitude. This fixed MEP value lies in the middle of the steepest portion of the stimulus response curve plotted on a logarithmic scale (Fisher et al, 2002;Vucic et al, 2006Vucic et al, , 2018. In the current study, the TS intensity required to elicit the MEPtarget at rest corresponded on average to 109% rMT (range 103-118 % rMT).…”
Section: Adaptive Threshold-hunting Techniquementioning
confidence: 52%
See 1 more Smart Citation
“…In Experiment 1, based on the corresponding literature, the hunting-threshold was defined as the TS intensity (expressed in percentage of the maximal stimulator output (%MSO)) required to elicit a MEPtarget in the relaxed FDI of 0.2 mV in peak-to-peak amplitude. This fixed MEP value lies in the middle of the steepest portion of the stimulus response curve plotted on a logarithmic scale (Fisher et al, 2002;Vucic et al, 2006Vucic et al, , 2018. In the current study, the TS intensity required to elicit the MEPtarget at rest corresponded on average to 109% rMT (range 103-118 % rMT).…”
Section: Adaptive Threshold-hunting Techniquementioning
confidence: 52%
“…The aim of the present study was to unravel the SICI modulation observed during MI through a methodological and conceptual reconsideration of: (i) the importance of CS intensity and (ii) the inhibitory process within M1 as an inherent feature of MI. To do so, we designed a pair of experiments in which we varied the CS intensity and determined the TS intensity required to maintain a fixed MEP amplitude for each condition using an adaptive threshold hunting technique (Awiszus et al, 1999;Fisher et al, 2002;Awiszus, 2003;Samusyte et al, 2018;Vucic et al, 2018). This method has been recently developed in order to overcome the potential limitations of conventional paired-pulse TMS protocols, such as large variability in MEP amplitude and a "floor/ceiling effect" when the observed inhibition leads to complete MEP suppression Cirillo et al, 2018;Van den Bos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cortical hyperexcitability appears to be an important pathogenic and diagnostic biomarker of ALS, mediated by an imbalance of inhibitory and facilitatory cortical circuit activity along with increased cortical neuronal excitability 1,3,8 . The evolution of cortical excitability changes with disease progression in ALS remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological processes underlying ALS development are complex and heterogenous, although the extent to which each neuronal populations are affected varies across individuals and disease sages 2 . Cortical hyperexcitability appears to be an important pathophysiological process in ALS, contributing to neurodegeneration via an anterograde glutamatergic excitotoxic process 1,3 . Support for this hypothesis is provided by transcranial magnetic stimulation (TMS) studies disclosing that cortical hyperexcitability is a specific and early feature of ALS, which precedes onset of muscle weakness, underlies development of clinical signs such as the split hand phenomenon, contributes to disease progression, and correlates with greater functional disability 4–8 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to SICI reduction, the MEP amplitude was also significantly increased, albeit only when recording from the hand and lower limb regions. The MEP amplitude reflects the density of corticomotoneuronal projections onto motor neurons 42 as well as the excitability of the local spinal cord circuitry 45 . The increase in MEP amplitude could be explained by cortical hyperexcitability, and is in keeping with previous studies in ALS patients 13,46,47 .…”
Section: Cortical Hyperexcitability and Alsmentioning
confidence: 99%